¿Es Medea “responsable” de matar a sus hijos? Medea de Eurípides, los dioses y la concepción aristotélica de la acción (Argos, 2025)
In this article we wonder if it is pertinent to analyse the character ofEuripides’ Medea and, more precisely, her filicide, in the light of Aristotle’sdoctrine of action. With regard to the heroine, it is doubtful and perhapsconfusing to talk about “responsibility” (in Aristotelian terms) becauseher motivations, as all tragic heroes’, are two-sided: faced to a superiorἀνάγκη he wants what he is forced to do as well. In addition, Medea is notan ordinary woman: she is an ontologically complex character that has ashare in the divine level, a share which is more crucial than what has usuallybeen emphasized.